Logical Choice Methodology of Factors Involved in Passenger Flow Estimation on a New Dedicated High-Speed Line - V. L. Perepel’Tsev (Вестник Научно-исследовательского института железнодорожного транспорта)
Dedicated high-speed railway lines (HSL) intended for train operation at speeds up to 350 - 400 kph represent in-novative tool capable to improve railway transport competitiveness within the served territories. The paper tackles logical choice aspects of the passenger traffic flow influencing factors on a new HSL. In this context analysis algorithm of passenger flow influencing factors across all the transport modes serving the route specified in the new HSL project may prove to be one of the factor defining solutions. There was conducted comprehensive socio-economic analysis of factors related to the HSL route. Also there were developed management proposals of socio-economic factors influencing determination and predic-tion of the HSL passenger flow. These proposals were formulated with due regard for each factor influence on the pas-senger flow across all the transport modes serving the new HSL route on the specific territory.